The Morbidity and Mortality Conference: A Century-Old Practice with Ongoing Potential for Future Improvement - de Vos, Marit S.; Verhagen, Merel J.; Hamming, Jaap F. (European Journal of Pediatric Surgery, 2023)
Objective To discuss practical strategies to consider for morbidity and mortality conferences (M&M).Materials and Methods This article reflects on (i) insights that can be drawn from the M&M literature, (ii) practical aspects to consider when organizing M&M, and (iii) possible future directions for development for this long-standing practice for routine reflection.Results M&M offers the opportunity to learn from past cases in order to improve the care delivered to future patients, thereby serving both educational and quality improvement purposes. For departments seeking to implement or improve local M&M practice, it is difficult that a golden standard or best practice for M&M is nonexistent. This is partly because comparative research on different formats is hampered by the lack of objective outcome measures to evaluate the effectiveness of M&M. Common practical suggestions include the use of (i) a skillful and active moderator; (ii) structured formats for case presentation and discussion; and (iii) a dedicated committee to guide improvement plans that ensue from the meeting. M&M practice is affected by various sociological factors, for which qualitative research methods seem most suitable, but in the M&M literature these are sparsely used. Moreover, aspects influencing an open and blame-free atmosphere underline how local teams should tailor the format to best fit the local context and culture.Conclusion This article presents practice guidance on how to organize and carry out M&M This practice for routine reflection needs to be tailored to the local setting, with attention for various sociological factors that are at play.
Keywords: morbidity and mortality conferences; team meetings; patient safety; quality improvement; continuing education